2021
DOI: 10.1099/mgen.0.000594
|View full text |Cite
|
Sign up to set email alerts
|

gbpA and chiA genes are not uniformly distributed amongst diverse Vibrio cholerae

Abstract: Members of the bacterial genus Vibrio utilize chitin both as a metabolic substrate and a signal to activate natural competence. Vibrio cholerae is a bacterial enteric pathogen, sub-lineages of which can cause pandemic cholera. However, the chitin metabolic pathway in V. cholerae … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…An obvious gap in our knowledge about V. cholerae O37 is the paucity of genome sequences of bacteria from this lineage. Understanding commonly used reference strains in the context of a species allows researchers to determine whether observations in a laboratory strain explain the species, a subset of the species, or just that strain in general [77,78]. Although some additional Sudanese genomes were published in 2017 [9], we still lack genome sequences for many of the interesting strains that have been discussed.…”
Section: Conclusion Open Questions and Future Directionsmentioning
confidence: 99%
“…An obvious gap in our knowledge about V. cholerae O37 is the paucity of genome sequences of bacteria from this lineage. Understanding commonly used reference strains in the context of a species allows researchers to determine whether observations in a laboratory strain explain the species, a subset of the species, or just that strain in general [77,78]. Although some additional Sudanese genomes were published in 2017 [9], we still lack genome sequences for many of the interesting strains that have been discussed.…”
Section: Conclusion Open Questions and Future Directionsmentioning
confidence: 99%
“…Many studies showed evidence of other Vibrio species causing disease on the surface of chitinaceous animals, for example Vibrio vulnificus colonizes on the surface of shellfish (Froelich & Noble, 2014). Vibrio parahaemolyticus used chitinase to colonize particulate chitin of copepods (Fennell, Blackwell, Thomson, & Dorman, 2021). Vibrio species are proved to metabolize chitin which is a favorite substrate for this group of bacteria.…”
Section: Introductionmentioning
confidence: 99%